Blood pressure variation during sub-maximal work performed by sedentary males from 32 to 55 years old - Ademir Tadeu Cardoso; Bárbara Regina Alvarez (Journal of Physical Education (Maringá), 2008)
This descriptive study, of exploratory purposes, investigated the blood (BP) variation during sub-maximal work performed on a bicycle ergometer. Subjects werw 25 sedentary males, from 32 to 55 years old. Exercise protocol was as suggested by Balke (1974): heart rate of 170 beats per minute or 85% of maximum heart rate. Blood pressure variation was calculated by the following equation: (Exercise BP - Resting BP)/ MET Statistical analysis included correlation and simple regression analysis. In some cases, systolic BP reached 250 mmHg, with a mean value of 198 mmHg. Double product from rest to exercise increased 300%, indicating low coronay protection in some individuals. Bp reactivity, as incicated by values of 8 mmHG/MET, points out to low cardio-respiratory fitness of other subjects. Another interesting finding was that as Physical Working Capacity (PWC 170) increased, BP variation tended to decrease for an average load of 145 watts. This results suggest that presure variation should be more carefully investigated for middle-aged, lowfit individuals, before entering an exercise program.